2014
DOI: 10.1155/2014/390865
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable Self Effects for Emotion Regulation: A Study of Chinese Major Depressive Outpatients

Abstract: Reappraisal is an adaptive emotion regulation strategy while the role of self-perspective in reappraisal process of depressed patients is largely unknown in terms of goals (valence/arousal) and tactics (detachment/immersion). In this study, 12 depressed individuals and 15 controls were scanned with MRI during which they either attend naturally to emotional stimuli, or adopt detachment/immersion strategy. Behaviorally, no group differences in self-reported emotion regulation effectiveness were found. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
2
17
1
Order By: Relevance
“…Pictures of stimuli were selected from the International Affective Picture System (IAPS) (Lang et al, 2008 ) based on normative ratings and were matched for content of scenes and people (Table S1 ). Valence and arousal ratings of pictures in each session and each condition were kept homogeneous, with non-significant differences in an ANOVA (emotion × reappraisal) ( P s > 0.05) (Wang et al, 2014 ). Twenty-four trials (12/positive; 12/negative) were included in the “detach/immerse” condition, and 36 trials (12/positive; 12/negative; 12/neutral) were included in the “attend” condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pictures of stimuli were selected from the International Affective Picture System (IAPS) (Lang et al, 2008 ) based on normative ratings and were matched for content of scenes and people (Table S1 ). Valence and arousal ratings of pictures in each session and each condition were kept homogeneous, with non-significant differences in an ANOVA (emotion × reappraisal) ( P s > 0.05) (Wang et al, 2014 ). Twenty-four trials (12/positive; 12/negative) were included in the “detach/immerse” condition, and 36 trials (12/positive; 12/negative; 12/neutral) were included in the “attend” condition.…”
Section: Methodsmentioning
confidence: 99%
“…Recent functional neuroimaging studies have mapped the brain systems that support reappraisal of emotional stimuli, which increases activation in executive control regions and decreases activation in subcortical regions such as the amygdala (Kanske et al, 2012 ; Perlman et al, 2012 ; Dillon and Pizzagalli, 2013 ; Smoski et al, 2013 ). In MDD, instructed reappraisal strategies instantiate hyper-/hypoactivation in the prefrontal cortex, such as diminished activation of the dorsal lateral prefrontal cortex (dlPFC) (Erk et al, 2010 ); enhanced activation of the anterior cingulate (Beauregard et al, 2006 ), lateral orbital-frontal cortex (Kanske et al, 2012 ), and right ventral medial prefrontal cortex (vmPFC) (Johnstone et al, 2007 ); and/or deficit in suppressing activation in limbic structures such as the amygdala and insula (Beauregard et al, 2006 ; Johnstone et al, 2007 ; Erk et al, 2010 ; Kanske et al, 2012 ), while the self-reported regulation success of depressed patients remains intact (Johnstone et al, 2007 ; Erk et al, 2010 ; Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using ICA analysis, the preprocessed time series of BOLD after head motion correction, smoothing, and spatial normalization were concatenated along time to form a 4-dimensional (4D) dataset. GIFT-toolbox [ 28 ] was used to decompose the 4D BOLD data into 20 mutually independent components. These analyses identified 12 RSNs for BOLD data.…”
Section: Methodsmentioning
confidence: 99%
“…Lang et al, 2012; Manber-Ball, Ramsawh, Campbell-Sills, Paulus, & Stein, 2013; Marissen, Meuleman, & Franken, 2010; Morris, Sparks, Mitchell, Weickert, & Green, 2012; New et al, 2009; Paul, Simon, Endrass, & Kathmann, 2015; Rabinak et al, 2014; Reinecke et al, 2015; Reinecke, Thilo, Filippini, Croft, & Harmer, 2014; Schulze et al, 2011; Smoski, Keng, Schiller, Minkel, & Dichter, 2013; Townsend et al, 2013; van der Meer et al, 2014; Wang et al, 2014; Woodward et al, 2015; Wu et al, 2015; Ziv, Goldin, Jazaieri, Hahn, & Gross, 2013). …”
Section: Figurementioning
confidence: 99%